2D light scattering static cytometry for label‐free single cell analysis with submicron resolution. (26th June 2015) - Xie, Linyan; Yang, Yan; Sun, Xuming; Qiao, Xu; Liu, Qiao; Song, Kun; Kong, Beihua; Su, Xuantao
Abstract Conventional optical cytometric techniques usually measure fluorescence or scattering signals at fixed angles from flowing cells in a liquid stream. Here we develop a novel cytometer that employs a scanning optical fiber to illuminate single static cells on a glass slide, which requires neither microfluidic fabrication nor flow control. This static cytometric technique measures two dimensional (2D) light scattering patterns via a small numerical aperture (0.25) microscope objective for label‐free single cell analysis. Good agreement is obtained between the yeast cell experimental and Mie theory simulated patterns. It is demonstrated that the static cytometer with a microscope objective of a low resolution around 1.30 μm has the potential to perform high resolution analysis on yeast cells with distributed sizes. The capability of the static cytometer for size determination with submicron resolution is validated via measurements on standard microspheres with mean diameters of 3.87 and 4.19 μm. Our 2D light scattering static cytometric technique may provide an easy‐to‐use, label‐free, and flow‐free method for single cell diagnostics. © 2015 International Society for Advancement of Cytometry